Use of analgesics in older individuals with special emphasis on organ failures: pitfalls and caveats - Asli Bahar Ucar; Mehmet Unaldi; Neslihan Kaytuoglu; Busra Erdem; Bilgen Ozkaya; Sezin Bozkurt; Pinar Vargun; Sennaz Sahin; Mehmet Can Girgin; Talha Ciftci; Ozgur Karcioglu (The Egyptian Journal of Internal Medicine, 2026)
Abstract Pain in older adults is highly prevalent and persistently undertreated, and its management becomes substantially more hazardous when renal, hepatic, or respiratory failure co-exists. Age-related pharmacokinetic changes — reduced hepatic blood flow and cytochrome P450 activity, declining glomerular filtration, and altered body composition — are compounded by pharmacodynamic changes, including heightened central nervous system sensitivity and reduced homeostatic reserve. This narrative review synthesises contemporary evidence and current prescribing frameworks into an organ-failure-stratified approach to analgesic selection. Paracetamol and topical agents remain the safest first-line options across all three organ failure states. Non-steroidal anti-inflammatory drugs should be avoided when the estimated glomerular filtration rate falls below 30 mL/min and are contraindicated in cirrhosis. Opioids remain indispensable for moderate-to-severe pain but require dose reduction, interval extension, and close monitoring: fentanyl and buprenorphine are preferred in renal failure, whereas morphine, codeine, and meperidine should be avoided; all opioid doses must be reduced in hepatic failure; and in respiratory failure or chronic obstructive pulmonary disease opioids should be given at the lowest effective dose and never combined with other central nervous system depressants. Adjuvant analgesics carry agent-specific organ restrictions. Frailty, cognitive impairment, and polypharmacy further modify risk. ‘Start low, go slow’ must be calibrated individually to the type and severity of organ dysfunction present.